Kahalani, The Heights Of Courage - A Tank Leader’s War On The Goal - Byrd, Richard (Teaching History: A Journal of Methods, 1993)
In the Yom Kippur War (October 6-25, 1973), Egypt and Syria nearly ended Israel’s perfect record in military conflicts with the Arabs. Maximum surprise was achieved by timing the attack for Yom Kippur, the most sacred day of Judaism. The two-front attack was well planned, coordinated, and executed. The Israelis had become overly confident in the capabilities of their equipment. Although outnumbered by the Soviet- and French-equipped Arabs, Israel’s weapons were superior in combat when used by properly trained personnel. Moreover, the Arabs used tactics unanticipated by Israel.